Multifaceted applications of dye-saturated biochar: Agronomic amelioration, thermochemical valorization, and catalytic efficacy in advanced environmental remediation paradigms - Sandra Ramachandran; Anshuman Gupta; Neelaambhigai Mayilswamy; Amrita Nighojkar; Balasubramanian Kandasubramanian (Cleaner Chemical Engineering)
The intensifying challenge of dye-laden industrial wastewater necessitates innovative, sustainable remediation technologies to mitigate ecological and human health risks. Sewage sludge-derived biochar (SSB) has emerged as a cost-effective and versatile adsorbent, attributed to its high surface area, hierarchical porosity, and diverse surface functional groups, which facilitate superior dye adsorption under both batch and continuous flow systems. This review provides a critical evaluation of SSB's adsorption performance, elucidating mechanisms such as π-π interactions, electrostatic attraction, and surface complexation. Regeneration methods, including thermal treatment, chemical washing, and solvent desorption, are analyzed in terms of efficiency and scalability. Furthermore, the secondary applications of dye-saturated biochar, including its use as a soil amendment to enhance microbial activity and nutrient retention, its valorization as a high-calorific energy source, and its role as a catalyst in advanced oxidation processes, are systematically explored. The review identifies key limitations, such as feedstock variability, competing ions in wastewater, and energy-intensive production processes, and proposes strategies for optimizing biochar synthesis and functionalization. By bridging laboratory-scale studies with industrial applications, this work delineates the economic and environmental viability of SSB and advances the development of scalable, sustainable wastewater treatment solutions.